Relative importance of biological nitrogen fixation and mineral uptake in high yielding soybean cultivars - Santachiara, Gabriel; Borrás, Lucas; Salvagiotti, Fernando; Gerde, José Arnaldo; Rotundo, José Luis (2018)
Backgrounds and aims: Soybean yield depends on total N uptake, N use efficiency, and harvest index. Nitrogen uptake relays on biological fixation (BNF) and soil absorption. Usually, BNF is considered a yield-related process. However, there is limited information on whether maximizing percent BNF (%BNF) is actually required to maximize N uptake and yield. Methods: Seventy cultivars were evaluated for total N uptake, N use efficiency, and harvest index. Biological N fixation was determined in a subset of cultivars. The harvest index of N derived from atmosphere and from soil was also assessed. Results: Yield was positively associated with total N uptake. Highest N uptake was not linked to increased %BNF. An inverse relationship between the amount of BNF (kgBNF) and soil N absorption was observed. Harvest index of N derived from BNF was 85%, while it was 77% for N derived from soil. Conclusions: Highest total N uptake was attained by different combinations of kgBNF and mineral soil N absorption. This showed that maximizing %BNF is not required to maximize yield. High %BNF played a pivotal role in determining neutral soil N balance. This is so even though N derived from BNF was more partitioned to seeds than N derived from soil.